2014
DOI: 10.28945/2072
|View full text |Cite
|
Sign up to set email alerts
|

Completion of Educational Doctorates: How Universities Can Foster Persistence

Abstract: With high attrition and long time-to-degree completion rates in education doctorate programs, it is important to identify ways for program administrators and faculty to foster student persistence. The purpose of this qualitative, phenomenological inquiry was to examine the beliefs, attitudes, and experiences of individuals who successfully completed doctoral degrees in the field of education in order to identify ways in which academic institutions can encourage persistence. Glasser's (1998) Choice Theory and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 48 publications
1
50
0
Order By: Relevance
“…While much research has explored student attrition, factors impacting student persistence in doctoral education has been less well-studied (Rockinson-Szapkiw et al, 2014). As the doctoral experience can be challenging, isolating, and lonely (Dickerson et al, 2014;Lovitts, 2001;Spaulding & Rockinson-Szapkiw, 2012), it is important to understand the resources and skills which facilitate students overcoming these challenges and persevering through their doctoral programs.…”
Section: Persistencementioning
confidence: 99%
See 3 more Smart Citations
“…While much research has explored student attrition, factors impacting student persistence in doctoral education has been less well-studied (Rockinson-Szapkiw et al, 2014). As the doctoral experience can be challenging, isolating, and lonely (Dickerson et al, 2014;Lovitts, 2001;Spaulding & Rockinson-Szapkiw, 2012), it is important to understand the resources and skills which facilitate students overcoming these challenges and persevering through their doctoral programs.…”
Section: Persistencementioning
confidence: 99%
“…A strong support network facilitates doctoral student persistence (Adorno, Cronley, & Smith, 2015;Dickerson et al, 2014;Martinez, Ordu, Della Sala, & McFarlane, 2013;McAlpine & Norton, 2006;Spaulding & Rockinson-Szapkiw, 2012). Personal supports outside of the academic program, such as partners, spouses, family, and friends, support student persistence (Adorno et al, 2015;Dickerson et al, 2014;Rockinson-Szapkiw et al, 2014). One study found that having a spouse increases the likelihood that students graduate from a doctoral program (Lott, Gardner, & Powers, 2009).…”
Section: Persistencementioning
confidence: 99%
See 2 more Smart Citations
“…The third stone cutter just smiles and said: 'I build cathedrals.' (Semler, p. 51;as cited in Bhindi & Duignan, 1997, p. 125) Finally, concerning mentoring deficiencies found within the doctoral mentoring process, Lovitts andNelson's (2000, as cited in Rockinson-Szapkiw, Spaulding, &Bade, 2014) work with graduate students states "the single most important factor in student decisions to continue or withdraw is the relationship with a faculty advisor [or mentor]" (p. 48). The importance of the mentor/Chair relationship, particularly in online higher education, is likewise highlighted in Nieto's (2016) recent research which suggests that dissertation "chairs do not see mentoring failure to be indicative of a lack of skill or knowledge [on their part], but rather a misalignment of purpose [with their students or institutionally] or a personality conflict with a student" (p. 97).…”
Section: Figure 2 Four Essential Elements Of Scholarly Leadershipmentioning
confidence: 99%